Pengaruh Penerapan Sistem Manajemen Mutu terhadap Kualitas Pelaksanaan Kegiatan Operasi dan Pemeliharaan (Studi Kasus: Tugas Pembantuan Operasi dan Pemeliharaan Daerah Irigasi Kedung Asem dan Daerah Irigasi Bodri Provinsi Jawa Tengah) - Amin, Mualim; Wibowo, M. Agung; Atmojo, Pranoto Samto (MEDIA KOMUNIKASI TEKNIK SIPIL, 2016)
A decrease in irrigation network performance system operation and maintenance are the impact of the operation management system and irrigation maintenance which does not suitable with the technical demands of the irrigation network design. The purpose of this study is to determine the effect of the application of quality management system in ministry of public works to the quality of the operations and maintenance on the Tasks Operation and Maintenance. The object of the research was in Kedung Asem and Bodri Irrigation Area, it was seen from three variables, namely: (1) the management of resources, (2) the implementation of the activities, (3) measurement, analysis and improvement. Data were obtained from observation andquestionnaire, and then were processed by using descriptive method and linear regression method. The results says that the quality management system in resource management is perceived as good enough category; the implementation activities, measurement, analysis and improvement were perceived good by the respondents. Identification of the quality of the operations and maintenance were also perceived good; further, performance index ratings of irrigation systems are performing well. The results of multiple linear regression equation is Y =12.883+1,181X1+0,449X2 +1,210X3, the conclusions hypothesis testing shows that the implication of quality management system give positive and significant effect on improving the quality of operations and maintenance work on the Tasks Operation and Maintenance of (DI) Kedung Asem and (DI) Bodri Irrigation Area.